Experimental Assessment of the Cyclic Behaviour of RC-DP Beam to Column Joints. Issue 5 (4th April 2022) - Caprili, Silvia; Chellini, Giuseppe; Mattei, Francesca; Romis, Federico; Salvatore, Walter
ABSTRACT: Corrosion represents one of the most important problems affecting the global behaviour of reinforced concrete (RC) buildings; in presence of aggressive environmental conditions reinforcing steel bars, as well as concrete, suffer from relevant modifications of the mechanical performance. Steel rebars show a high decrease of the deformation capacity, with reduction of the elongation to maximum load up to the 50% in case of TempCore® grades. This can cause unexpected brittle failures related to the premature achievement of ultimate rotation or, even worst, shear capacity of structural elements. To mitigate these problems, actual European standards for constructions foresee the adoption of specific precautions such as the increase of concrete strength class, of the concrete cover, of higher diameter; these tools allow to reduce the effects of corrosion without deleting the origin of the matter. During the last years, otherwise, another typology of reinforcing steel – characterized by a typical Dual-Phase (DP) microstructure – was developed with the aim of directly preventing corrosion initiation. Due to their microstructure, in which martensite is embedded in the ferrite matrix, Dual-Phase steels are less exposed to corrosion; on the other hand, being characterized by a not-defined yielding stress-strain plateau, specific rules need to be elaborated for their employment in civil applications. In the present paper, the experimental test campaign performed on reinforced concrete internal and external joints with Dual-Phase steel rebars is deeply described together with results' critical discussion. The paper is preparatory for the elaboration of technical models to be used in the design of RC-DP structures.